INNOVATIVE MODELS FOR MANAGING THE PRIMARY HEALTH CARE SYSTEM (regional experience) - N. N. Zubareva (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The article analyzes the practice of applying innovative models of primary health care system management in the framework of the Belgorod region project «Health Management». The special place is given to the evaluation of innovative models of primary health care organization on the Belgorod region’s territory. The experience of medical care for adults and children in urban and rural areas by general practitioners (family doctors) is presented. Changes in the structure of primary care physician admission in regional medical institutions are shown. The expediency of innovative modeling is confirmed by the presence of organizational and medical-demographic effects.